Polyurethane foam and method for producing polyurethane foam
The polyurethane foam formulation with specific polyol components and hollow particles addresses heat insulation and strength issues, resulting in a foam with superior thermal performance and mechanical strength for sheet-like materials.
Patent Information
- Application Number
- JP2023096702
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional polyurethane foams suffer from insufficient heat insulation due to convection heat transfer through open cells and require improved strength, especially when used in sheet form.
A polyurethane foam formulation using specific polyol components with hydroxyl values of 25 to 60 mgKOH/g, number average functional groups of 3 to 4, and oxyethylene units less than 20% by weight, combined with hollow particles at 5 to 30% by weight, along with a dispersant, catalyst, and stabilizer, to enhance heat insulation and strength.
The solution provides polyurethane foam with excellent heat insulation and strength, suitable for sheet-like applications, achieving low thermal conductivity and high tensile strength.
Smart Images

Figure 2024178520000001 
Figure 2024178520000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyurethane foam and a method for producing the polyurethane foam. [Background technology]
[0002] 2. Description of the Related Art Polyurethane foams have been considered as heat insulating materials because of their excellent heat insulating properties and moldability (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-64050 Summary of the Invention [Problem to be solved by the invention]
[0004] In conventional urethane foams, open cells are easily formed, which can cause convection heat transfer and result in insufficient insulation, and further improvement is therefore required. In addition, since it is anticipated that the urethane foam will be molded into sheets or the like for use, it is required to have high strength. An object of the present invention is to provide a polyurethane foam having excellent heat insulation and strength, and a method for producing the same. [Means for solving the problem]
[0005] The present inventors conducted extensive research to solve the above problems and arrived at the present invention. That is, the present invention is as follows. [1] A polyurethane foam obtained by reacting materials including a polyol component (A), an organic polyisocyanate component (B), a blowing agent (C), a catalyst (D), a foam stabilizer (E) and hollow particles (F), wherein the polyol component (A) satisfies all of the following (1) to (3), and the amount of the hollow particles (F) is 5 to 30% by weight based on the weight of the polyurethane foam. (1) the polyol component (A) has a hydroxyl value of 25 to 60 mgKOH / g; (2) the number average functionality of the polyol component (A) is 3 to 4; (3) The weight proportion of oxyethylene units contained in the polyol component (A) is 20% by weight or less based on the weight of the polyol component (A). [2] The polyurethane foam according to claim 1, wherein the material further comprises a dispersant (G). [3] Polyurethane foam core density (kg / m 3 ) is 30 to 50. [4] A method for producing a polyurethane foam according to any one of [1] to [3], comprising: step 1 of preparing a polyol composition containing a polyol component (A) and hollow particles (F); and step 2 of reacting the polyol composition with an organic polyisocyanate component (B) in the presence of a blowing agent (C), a catalyst (D) and a foam stabilizer (E). [5] The method for producing a polyurethane foam according to [4], wherein a dispersant (G) is used in step 1. [6] Polyurethane foam core density (kg / m 3 ) is 30 to 50. Effect of the Invention
[0006] According to the present invention, it is possible to provide a polyurethane foam having excellent heat insulation and strength, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] (Polyurethane foam) The polyurethane foam of the present invention is produced by reacting materials including a polyol component (A), an organic polyisocyanate component (B), a blowing agent (C), a catalyst (D), a foam stabilizer (E) and hollow particles (F).
[0008] In the present invention, the polyol component (A) satisfies all of the following requirements (Requirement 1), (Requirement 2), and (Requirement 3). By satisfying the following requirements, it is possible to provide a polyurethane foam having excellent heat insulation properties and strength. (Requirement 1) The polyol component (A) has a hydroxyl value of 25 to 60 mgKOH / g. (Requirement 2) The polyol component (A) has a number-average functionality of 3 to 4. (Requirement 3) The weight ratio of oxyethylene units contained in the polyol component (A) is 20% by weight or less based on the weight of the polyol component (A).
[0009] Requirement 1 will be described. In the present invention, the hydroxyl value of the polyol component (A) is 25 to 60 mgKOH / g. From the viewpoint of the strength of the resulting polyurethane foam, the hydroxyl value of the polyol component (A) is preferably 28 mgKOH / g or more, more preferably 30 mgKOH / g or more. From the viewpoint of the elasticity of the resulting polyurethane foam, the hydroxyl value of the polyol component (A) is preferably 55 mgKOH / g or more, more preferably 52 mgKOH / g or more. In the present specification, the unit of the hydroxyl value may be omitted, and only the numerical value may be described. The hydroxyl value can be measured according to the method specified in JIS K0070.
[0010] In the present invention, one type of polyol or two or more types of polyols can be used as the polyol component (A). When two or more types of polyols are used, the hydroxyl value of the polyol component (A) can be calculated by weighted average. For example, when the polyol component (A) has a hydroxyl value of OHV, 1 Polyol (a1) with a hydroxyl value of OHV 2and a polyol (a2) of the formula (A) in which the weight ratio [weight of polyol (a1):weight of polyol (a2)] is W1:W2, the hydroxyl value OHV of the polyol component (A) is A can be calculated using the following formula: OHV A =(OHV 1 ×W1+OHV 2 ×W2) / (W1+W2)
[0011] Requirement 2 will be explained. In the present invention, the number-average functionality of the polyol component (A) is 3 to 4. The number-average functionality of the polyol component (A) is preferably 3.1 to 3.9 from the viewpoint of excellent elasticity and strength. The polyol component (A) may have a number-average functionality of 3 to 4, and the component (A) may contain a polyol having 5 or more functional groups per molecule and / or a polyol having 2 functional groups per molecule. The number-average functionality of the polyol component (A) can be set within the above range by adjusting the type and amount of the polyol used as the polyol component (A). The number-average functionality of the polyol component (A) can be measured, for example, by the number-average molecular weight and hydroxyl value by gel permeation chromatography. The number-average functionality of the polyol components used in the examples was measured by this method.
[0012] Requirement 3 will now be described. In the present invention, the weight percentage of oxyethylene units contained in polyol component (A) is 20% by weight or less based on the weight of polyol component (A). From the viewpoint of excellent heat insulation and dimensional stability of the urethane foam, the weight percentage of oxyethylene units in polyol component (A) is preferably 18% by weight or less, and more preferably 15% by weight or less, based on the weight of polyol component (A). The weight percentage of oxyethylene units contained in polyol component (A) can be set within the above range by adjusting the type and amount of polyol used as polyol component (A). The weight percentage of oxyethylene units contained in polyol component (A) can be set within the above range, for example. 1 It can be measured by H-NMR.
[0013] The method for calculating the weight percentage of oxyethylene units will be specifically described. The signal from the methylene group to which a hydroxyl group is bonded is observed at about 3.6 ppm, and the signal from the methyl group is observed at about 1.1 ppm (deuterated chloroform is used as the solvent). The weight percentage of oxyethylene units is calculated using the following formula. Weight ratio of oxyethylene units = [33(ab) / (33a+23b)]×100 In the formula, a is the integral value of the signal derived from a methylene group bonded to a hydroxyl group at approximately 3.6 ppm; and b is the integral value of the signal derived from a methyl group at approximately 1.1 ppm.
[0014] Examples of the polyol used as the polyol component (A) include polyether polyols, etc. Examples of the polyether polyols include alkylene oxide (hereinafter sometimes abbreviated as AO) adducts of active hydrogen group-containing compounds, etc. Examples of the active hydrogen-containing compound include polyhydric alcohols (preferably dihydric to hexahydric alcohols), dihydric to hexahydric hydroxyl group-containing compounds other than alcohols, amino group-containing compounds, and thiol group-containing compounds.
[0015] Examples of polyhydric alcohols include dihydric alcohols having 2 to 20 carbon atoms [aliphatic diols (ethylene glycol, propylene glycol, 1,3- or 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, etc.) and alicyclic diols (cyclohexanediol, cyclohexanedimethanol, etc.)], trihydric alcohols having 3 to 20 carbon atoms [aliphatic triols (glycerin, trimethylolpropane, etc.)], and tetrahydric to hexahydric alcohols having 4 to 20 carbon atoms [aliphatic polyols (pentaerythritol, etc.)].
[0016] Examples of divalent to tetravalent hydroxyl group-containing compounds other than alcohols include divalent to tetravalent polyhydric phenols (hydroquinone, bisphenol A, bisphenol F, bisphenol S, 1,3,6,8-tetrahydroxynaphthalene, 1,4,5,8-tetrahydroxyanthracene, etc.), polybutadiene polyols, castor oil polyols, and condensates of phenol and formaldehyde (novolak, etc.).
[0017] Examples of the amino group-containing compound include amines, polyamines, and amino alcohols. Specific examples include ammonia, alkylamines having 1 to 20 carbon atoms (butylamine, etc.), aniline, aliphatic polyamines (ethylenediamine, hexamethylenediamine, etc.), heterocyclic polyamines (piperazine, N-aminoethylpiperazine, etc.), alicyclic polyamines (dicyclohexylmethanediamine, isophoronediamine, etc.), aromatic polyamines (phenylenediamine, tolylenediamine, diphenylmethanediamine, etc.), alkanolamines (monoethanolamine, diethanolamine, triethanolamine, etc.), polyamide polyamines obtained by condensation of dicarboxylic acid with an excess of polyamine, polyether polyamines, hydrazines (hydrazine, monoalkylhydrazine, etc.), and dicyandiamide.
[0018] The thiol group-containing compound may be a polythiol compound. The polythiol may be a divalent to tetravalent polythiol. Specific examples include ethanedithiol and 1,6-hexanedithiol.
[0019] Examples of AO include AO having 2 to 4 carbon atoms, such as ethylene oxide (hereinafter sometimes abbreviated as EO), propylene oxide (hereinafter sometimes abbreviated as PO), and butylene oxide (hereinafter abbreviated as BO). PO and BO may be linear or branched. From the viewpoint of the strength of the resulting polyurethane foam, AO preferably contains PO, and more preferably is a combination of PO and EO. When two or more AOs are contained, the addition form may be block addition or random addition, or a combination of these may be used.
[0020] From the viewpoint of the strength and elasticity of the resulting polyurethane foam, the polyol component (A) is preferably an AO adduct of a trihydric to hexahydric alcohol, and more preferably an AO adduct of glycerin, an AO adduct of pentaerythritol, or a combination thereof.
[0021] The organic polyisocyanate (B) is not particularly limited as long as it is an organic polyisocyanate used in flexible polyurethane foams, and examples thereof include aromatic polyisocyanates, aliphatic polyisocyanates, alicyclic polyisocyanates, araliphatic polyisocyanates, modified products thereof (such as modified products containing urethane groups, carbodiimide groups, allophanate groups, urea groups, biuret groups, isocyanurate groups, and oxazolidone groups), and mixtures of two or more of these.
[0022] Examples of aromatic polyisocyanates include aromatic diisocyanates having 6 to 16 carbon atoms excluding the carbon atoms in the NCO groups (in the following polyisocyanates, the carbon atoms in the NCO groups are excluded when the carbon number is stated as "carbon number"), aromatic triisocyanates having 6 to 20 carbon atoms, and crude products of these isocyanates. Specific examples include 1,3- or 1,4-phenylene diisocyanate, 2,4- or 2,6-tolylene diisocyanate (TDI), crude TDI, 2,4'- or 4,4'-diphenylmethane diisocyanate (MDI), polymethylene polyphenylene polyisocyanate (crude MDI), naphthylene-1,5-diisocyanate, and triphenylmethane-4,4',4''-triisocyanate.
[0023] Examples of the aliphatic polyisocyanate include aliphatic diisocyanates having 6 to 10 carbon atoms. Specific examples include 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate.
[0024] Examples of the alicyclic polyisocyanate include alicyclic diisocyanates having a carbon number of 6 to 16. Specific examples include isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, and norbornane diisocyanate.
[0025] The araliphatic isocyanate may be an araliphatic diisocyanate having a carbon number of 8 to 12. Specific examples include xylylene diisocyanate and α,α,α',α'-tetramethylxylylene diisocyanate. A specific example of the modified polyisocyanate is carbodiimide-modified MDI.
[0026] Among these organic polyisocyanates (B), from the viewpoints of reactivity and moldability, aromatic polyisocyanates are preferred, and TDI is more preferred.
[0027] The physical properties of the polyurethane foam of the present invention can be adjusted by adjusting the ratio of isocyanate groups (NCO groups) to active hydrogen atoms in the materials for producing the polyurethane foam. In the present invention, the ratio of isocyanate groups (NCO groups) to active hydrogen atoms (also called the isocyanate index) is preferably 0.5 to 2, more preferably 0.6 to 1.5, and particularly preferably 0.8 to 1.3, from the viewpoints of heat insulation and moldability. The isocyanate index is calculated as the ratio (%) of the equivalent of the isocyanate group in (D) to the equivalent of the active hydrogen atom-containing group in the material for producing the polyurethane foam.
[0028] Examples of the blowing agent (C) include water, liquefied carbon dioxide gas, and low-boiling compounds having a boiling point of -5 to 70°C.
[0029] Examples of the low-boiling compounds include hydrogen atom-containing halogenated hydrocarbons and low-boiling hydrocarbons. Specific examples of hydrogen atom-containing halogenated hydrocarbons and low-boiling hydrocarbons include methylene chloride, HCFCs (hydrochlorofluorocarbons) (HCFC-123, HCFC-141b, HCFC-142b, etc.), HFCs (hydrofluorocarbons) (HFC-152a, HFC-356mff, HFC-236ea, HFC-245ca, HFC-245fa, HFC-365mfc, etc.), butane, pentane, and cyclopentane.
[0030] As the foaming agent (C), water is preferred from the viewpoint of moldability. When water is used as the blowing agent (C), the amount of water used is preferably 1.0 to 5.0 parts by weight, more preferably 1.5 to 4.5 parts by weight, per 100 parts by weight of the total weight of the polyol component, hollow particles and dispersant, from the viewpoints of the core density and heat insulation of the foam.
[0031] Examples of catalyst (D) include tertiary amines and their carboxylates, such as triethylenediamine, bis(2-dimethylaminoethyl)ether, and N,N,N',N'-tetramethylhexamethylenediamine; metal carboxylates, such as potassium acetate, potassium octoate, and stannous octoate; and organometallic compounds, such as dibutyltin dilaurate and stannous octoate. Catalyst (D) may be commercially available. Examples of commercially available catalysts include "TEDA-L33" (triethylenediamine / dipropylene glycol = 33 / 67 wt% solution) manufactured by Tosoh Corporation, "TOYOCAT ET" (bis(2-dimethylaminoethyl)ether / dipropylene glycol = 70 / 30 wt% solution), and "Neostan U-28" (stannous octoate) manufactured by Nitto Kasei Co., Ltd. Catalyst (E) may be used alone or in combination of two or more types. As the catalyst, from the viewpoint of moldability, triethylenediamine, bis(2-dimethylaminoethyl) ether, stannous octoate, and combinations of two or more of these are preferred.
[0032] From the viewpoints of moldability and curing time, the amount of catalyst (D) used is preferably 0.01 to 6.0 parts by weight, and more preferably 0.05 to 4.0 parts by weight, per 100 parts by weight of the total weight of the polyol component, hollow particles, and dispersant.
[0033] As the foam stabilizer (E), known foam stabilizers (such as silicone-based foam stabilizers and non-silicone-based foam stabilizers) used in the production of polyurethane foam can be used. Specific examples include those available on the market such as "SZ-1959", "SF-2904", "SZ-1142", "SZ-1720", "SZ-1675t", "SF-2936F", "SZ-3601", "SRX-294A", "SH-193", and "L-580" manufactured by Toray Dow Corning Co., Ltd., "L-540" and "L-3601" manufactured by Nippon Unicar Co., Ltd., "L-626" manufactured by Momentive Performance Materials Co., Ltd., and "B8715 LF2" manufactured by Evonik Degussa Japan Co., Ltd. As the foam stabilizer, "L-580" manufactured by Toray Dow Corning Co., Ltd. is preferred.
[0034] From the viewpoints of moldability and impact resilience, the amount of foam stabilizer (E) used is preferably 0.2 to 5.0 parts by weight, and more preferably 0.5 to 3.0 parts by weight, per 100 parts by weight of the total weight of the polyol component, hollow particles and dispersant.
[0035] As the hollow particles (F), particles having a spherical external shape and a hollow inside can be used. The structure of the hollow particles (external shape, outer diameter, inner diameter, etc.) can be measured using images taken with a transmission electron microscope (TEM). Specifically, the particle diameter (outer diameter) and inner diameter are measured at five or more points passing through the center of the hollow particle. The average values of the measurement results are taken as the average outer diameter (average particle diameter) and average inner diameter. Furthermore, the porosity of the hollow particle is calculated from the following formula (2) using the average outer diameter (average particle diameter) and average inner diameter. (Average inner diameter) 3 / (average particle size) 3 ×100 (2)
[0036] The average outer diameter of the hollow particles (F) is preferably 100 nm or more, more preferably 300 nm or more, and preferably 10 μm or less, more preferably 5 μm or less, from the viewpoint of foam moldability when the polyurethane foam is molded into a thin film. The porosity of the hollow particles (F) is preferably 30 vol% or more, more preferably 40 vol% or more, and preferably 90 vol% or less, more preferably 85 vol% or less, based on the volume of the hollow particles, from the viewpoints of production and heat insulation.
[0037] Examples of the hollow particles (F) include hollow particles made of polystyrene and hollow particles containing a metal oxide (e.g., silica, etc.). Commercially available hollow particles (F) may be used. Examples of commercially available hollow particles include PS hollow particles (average outer diameter: 1 μm, average porosity 80 vol%) manufactured by Sansui Co., Ltd., PS hollow particles (average outer diameter: 4 μm, porosity 60 vol%) manufactured by Sekisui Polymatech Co., Ltd., and PS hollow particles (average outer diameter: 0.5 μm, porosity 40 vol%) manufactured by Sekisui Polymatech Co., Ltd.
[0038] In the present invention, the amount of hollow particles (F) is 5 to 30% by weight based on the weight of the polyurethane foam. By setting the amount of hollow particles to 5 to 30% by weight, a polyurethane foam having excellent heat insulation properties and excellent strength can be provided. From the viewpoint of heat insulation, the amount of hollow particles (F) based on the weight of the polyurethane foam is preferably 5.5% by weight or more, more preferably 6.0% by weight or more, and is preferably 29% by weight or less, more preferably 25% by weight or less.
[0039] In the present invention, the material for producing a polyurethane foam preferably contains a dispersant (G) in addition to the polyol component (A), the organic polyisocyanate component (B), the blowing agent (C), the catalyst (D), the foam stabilizer (E) and the hollow particles (F). The dispersant (G) has a function of dispersing the hollow particles (F) in the polyol component (A). By using the dispersant (G), the dispersibility of the hollow particles (F) in the polyurethane foam material can be improved.
[0040] Examples of the dispersant (G) include aliphatic polyether type nonionic surfactants, AO adducts of polyhydric phenols, and AO adducts of arylalkylphenols (having a carbon number of 14 to 62; styrenated phenol, etc.). The dispersant (G) may be used alone or in combination of two or more. Examples of the aliphatic polyether type nonionic surfactants include ethylene oxide adducts of polypropylene glycol and polyoxyethylene alkyl ether. Examples of the AO adducts of polyhydric phenols include EO adducts of bisphenols. From the viewpoint of dispersibility of the hollow particles (F), preferred dispersants (G) are ethylene oxide adducts of polypropylene glycol, AO adducts of bisphenol A, and AO adducts of styrenated phenol.
[0041] As the dispersant (G), commercially available products may be used. Examples of such commercially available products include "Newpol PE-64" manufactured by Sanyo Chemical Industries, Ltd., "Newpol BPE-100" manufactured by Sanyo Chemical Industries, Ltd., "Newpol BP-5P" manufactured by Sanyo Chemical Industries, Ltd., "Eleminol HB-12" manufactured by Sanyo Chemical Industries, Ltd., and "Naroacty ID-60" manufactured by Sanyo Chemical Industries, Ltd.
[0042] The amount of the dispersant (G) is preferably 0.01 to 2.0 parts by weight, and more preferably 0.1 to 1.0 part by weight, based on 100 parts by weight of the total weight of the polyol component, the hollow particles, and the dispersant.
[0043] The material for the polyurethane foam of the present invention may contain other auxiliary agents (H) in addition to the polyol component (A), the organic polyisocyanate component (B), the blowing agent (C), the catalyst (D), the foam stabilizer (E), the hollow particles (F) and the dispersant (G). Other auxiliaries (H) include colorants (dyes and pigments), plasticizers (phthalates and adipates, etc.), organic fillers (synthetic short fibers, hollow microspheres made of thermoplastic or thermosetting resins, etc.), flame retardants (phosphate esters and halogenated phosphate esters, etc.), age inhibitors (triazoles and benzophenones, etc.), and antioxidants (hindered phenols and hindered amines, etc.).
[0044] The total amount of the other auxiliary (H) used is preferably 0 to 50 parts by weight, more preferably 0 to 30 parts by weight, based on 100 parts by weight of the polyol component (A).
[0045] The core density of the polyurethane foam of the present invention is preferably 30 kg / m from the viewpoint of the strength of the polyurethane foam. 3 More preferably, it is 31 kg / m 3 The core density of the polyurethane foam is preferably 50 kg / m from the viewpoint of heat insulation. 3 More preferably, it is 48 kg / m or less. 3 The following is the result.
[0046] (Method of manufacturing polyurethane foam) The polyurethane foam of the present invention is preferably produced by a production method including step 1 of preparing a polyol composition containing a polyol component (A) and hollow particles (F), and step 2 of reacting the polyol composition with an organic polyisocyanate component (B) in the presence of a blowing agent (C), a catalyst (D) and a foam stabilizer (E). By producing the polyurethane foam by this production method, a polyurethane foam having excellent heat insulation properties and strength can be obtained.
[0047] Step 1 is a step of preparing a polyol composition containing a polyol component (A) and hollow particles (F). The polyol component (A) and hollow particles (F) may be the same as the polyol component (A) and hollow particles (F) used as materials for polyurethane foam.
[0048] The polyol composition can be prepared by mixing the polyol component (A) and the hollow particles (F). As a mixing device, for example, a bead mill can be used. The mixing conditions can be appropriately set depending on the materials used and their blending ratios.
[0049] In step 1, it is preferable to use a dispersant (G) together with the polyol component (A) and the hollow particles (F). The use of the dispersant (G) improves the dispersibility of the hollow particles (F), and can improve the uniformity of the structure of the resulting polyurethane foam and the moldability of the foam. The dispersant (G) can be the same as the dispersant (G) used as a material for polyurethane foam.
[0050] The amount of the dispersant (G) used is preferably from 0.01 to 2.0 parts by weight, and more preferably from 0.1 to 1.0 part by weight, based on 100 parts by weight of the polyol composition.
[0051] Step 2 is a step of reacting the polyol composition obtained after carrying out step 1 with the organic polyisocyanate component (B) in the presence of a blowing agent (C), a catalyst (D) and a foam stabilizer (E). The organic polyisocyanate component (B), the blowing agent (C), the catalyst (D) and the foam stabilizer (E) used in step 2 may be the same as the organic polyisocyanate component (B), the blowing agent (C), the catalyst (D) and the foam stabilizer (E) used as materials for polyurethane foam.
[0052] Step 2 can be carried out, for example, by the following method. First, a polyol composition, a blowing agent (C), a catalyst (D), a foam stabilizer (E), and other auxiliary agents (H) used as necessary are mixed to prepare a mixture (hereinafter also referred to as "first mixture"). Next, an organic polyisocyanate component (B) is added to the first mixture and mixed. Next, an organic polyisocyanate component (B) is added to the first mixture and mixed. This causes the polyol component contained in the first mixture to react with the organic polyisocyanate component (B) (urethanization reaction). Next, a reaction product generated by the reaction between the first mixture and the organic polyisocyanate component (B) is foamed to obtain a polyurethane foam.
[0053] Step 2 may be performed using a foaming machine and / or agitator, or may be performed using a closed or open mold (made of metal, resin, or paper). The mixing conditions (mixing temperature, mixing time, etc.) of the first mixture and the mixing conditions (mixing temperature, mixing time, etc.) of the first mixture and the organic polyisocyanate component (B) can be appropriately set in consideration of the materials and amounts used. The foaming conditions (foaming temperature, foaming time) can also be appropriately set in consideration of the types and amounts of the foaming agent and the components used.
[0054] (Polyurethane foam applications) The polyurethane foam of the present invention and the polyurethane foam obtained by the production method of the present invention are excellent in strength and heat insulation, and therefore suitable for use as a heat insulating material. The polyurethane foam of the present invention has excellent strength even when formed into a sheet shape, and is therefore particularly preferable for use as a sheet-shaped heat insulating material. When the polyurethane foam is used in a sheet shape, the thickness can be, for example, 10 μm to 100 mm. When used as a sheet-shaped heat insulating material, it can be used as a heat insulating material for, for example, a thermoelectric conversion module or a cooler (small refrigerator for consumer use, small cooler for medical or experimental use for industrial use, etc.), a generator (generator using automobile or industrial waste heat, generator incorporated in cogeneration, nuclear battery for space development, etc.), etc. EXAMPLES
[0055] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited thereto. Unless otherwise specified, parts are parts by weight. The reaction temperature includes a range of ±10°C.
[0056] [Production Example 1: Production of polyol (a-1)] Using potassium hydroxide as a catalyst [catalyst amount 0.3 wt % (based on the weight of the reaction product)], 7,878 parts of propylene oxide (PO) were added to 136 parts of pentaerythritol at a reaction temperature of 120°C to obtain a polyether polyol (a-1) having a functionality of 4, a hydroxyl value of 28 mgKOH / g, and an EO unit content of 0 wt %.
[0057] [Production Example 2: Production of polyol (a-2)] Using potassium hydroxide as a catalyst [catalyst amount 0.3 wt% (based on the weight of the reaction product)] to 136 parts of pentaerythritol, 6035 parts of PO were added at a reaction temperature of 120°C, and then 842 parts of EO were added to obtain a polyether polyol (a-2) having a functionality of 4, a hydroxyl value of 32 mgKOH / g, and an EO unit content of 12 wt%.
[0058] [Production Example 3: Production of polyol (a-3)] To 92 parts of glycerin, potassium hydroxide was used as a catalyst [catalyst usage amount 0.3 wt % (based on the weight of the reaction product)], and at a reaction temperature of 120° C., 2615 parts of PO, then 323 parts of EO, and then 206 parts of PO were added to obtain a polyether polyol (a-3) having a functionality of 3, a hydroxyl value of 52 mgKOH / g, and an EO unit content of 10 wt %.
[0059] [Production Example 4: Production of polyol (a-4)] Using potassium hydroxide as a catalyst [catalyst usage amount 0.3 wt% (based on the weight of the reaction product)] to 92 parts of glycerin, 2573 parts of PO were added at a reaction temperature of 120°C, and then 140 parts of EO were added to obtain a polyether polyol (a-4) having a functionality of 3, a hydroxyl value of 60 mgKOH / g, and a terminal EO unit content of 5 wt%.
[0060] [Method of measuring physical properties of polyol] The physical properties of the polyols obtained in Production Examples 1 to 4 were measured by the following methods. (1) Hydroxyl value The hydroxyl value of the polyol was measured according to the method specified in JIS K0070. (2) Number of functional groups The number-average functionality of the polyol was calculated by measuring the number-average molecular weight and hydroxyl value of the polyol by gel permeation chromatography. <Gel permeation chromatography conditions> Device body: HLC-8420 (Tosoh Corporation) Column: Tosoh Corporation TSKgel Super H4000, H3000, H2000 Detector: RI (Refractive Index) Eluent:THF Eluent flow rate: 0.6ml / min Column temperature: 40℃ Sample concentration: 0.25% by weight Injection volume: 10μl Standard material: TSK STANDARD POLYSTYRENE manufactured by Tosoh Corporation Data processing software: EcoSEC Elite-WS analysis (Tosoh Corporation) (calculation method) Average number of functional groups=Mn / (56100)×OHV In the formula, Mn is the number average molecular weight measured by GPC; OHV is the hydroxyl value. (3) EO unit content The weight proportion of the oxyethylene unit in the polyol component (A) was calculated by the method described above for calculating the weight proportion.
[0061] [Production of polyol compositions (P-1) to (P-6)] Polyol compositions (P-1) to (P-6) were prepared by dispersing hollow particles in a polyol component using the types and amounts (parts) of polyol, hollow particles (F), and dispersant (G) shown in Table 1. The polyol composition was prepared using a bead mill [Ultraviscomill (manufactured by Imex)] under conditions of a liquid feed rate of 1 kg / hour, a disk peripheral speed of 6 m / sec, and 80 volume % filling of glass beads with a particle size of 0.4 mm, with two passes.
[0062] [Table 1]
[0063] The components listed in Table 1 are as follows. <Polyol component (A)> Polyol (a-1): Polyether polyol obtained in Production Example 1 Polyol (a-2): Polyether polyol obtained in Production Example 2 Polyol (a-3): Polyether polyol obtained in Production Example 3 Polyol (a-4): Polyether polyol obtained in Production Example 4 <Hollow particle (F)> (F-1): PS hollow particles manufactured by Sansui Co., Ltd. (average outer diameter: 1 μm, average porosity 80 vol%) (F-2): PS hollow particles manufactured by Sekisui Polymatec Co., Ltd. (average outer diameter: 4 μm, average porosity 60 vol%) (F-3): PS hollow particles manufactured by Sekisui Polymatec Co., Ltd. (average outer diameter: 0.5 μm, average porosity 40 vol%) <Dispersant (G)> (G-1): Sanyo Chemical Industries, Ltd.'s "Newpol PE-64", an ethylene oxide adduct of polypropylene glycol (G-2): Sanyo Chemical Industries, Ltd.'s "Newpol BPE-100", an EO adduct of bisphenol A (G-3): Sanyo Chemical Industries, Ltd. "Naroacty ID-60", polyoxyethylene alkyl ether
[0064] <Examples 1 to 6, Comparative Examples 1 to 2> Using a mixer, the materials shown in Table 2 [polyol composition (P) or polyol (a-1), blowing agent (C), catalyst (D) and foam stabilizer (E)] were mixed in the amounts (parts by weight) shown in Table 2, and the mixture was stirred by hand mixing (a method in which a stirring blade is inserted into a container to stir) to obtain a mixture. The liquid temperature of the mixture was adjusted to 25°C. The mixture adjusted to 25°C was mixed with the organic polyisocyanate (B) whose liquid temperature was adjusted to 25°C in the amount (parts by weight) shown in Table 2, and the mixture was stirred by hand mixing at 3000 rpm for 6 to 20 seconds to obtain a mixed liquid. The mixture was poured into a rectangular paper mold of 400 mm x 400 mm x 200 mm with an open top, and left to foam for 24 hours at 25°C and 50% humidity to produce a soft polyurethane slab foam. The foaming conditions were as follows: <Foaming conditions> Mold: 400mm x 400mm x 200mm rectangular paper box Mixing method: Mix with a mixer at 3000 rpm Raw material temperature: 25±2℃ Amount of raw material used: 300g of (a1) Cure conditions: 25°C, 1 day (24 hours)
[0065] Core density (kg / m) of polyurethane slab foam (hereinafter referred to as "polyurethane foam") after standing overnight 3 ), tensile strength (N / cm2 ), breaking elongation (%) and thermal conductivity (W / m K) were measured using the following methods. The measurement results are shown in Table 2.
[0066] <Measurement method> (1) Foam core density According to the method specified in JIS K6400, the core density of polyurethane foam (kg / m 3 ) was measured. The core density was 30 kg / m 3 ~50kg / m 3 It is preferable that:
[0067] (2) Tensile strength According to the method specified in JIS K6400, the tensile strength of polyurethane foam (N / cm 2 The tensile strength was measured at 1.1 N / cm 2 More preferably, it is equal to or greater than this.
[0068] (3) Breaking elongation The elongation at break (%) of the polyurethane foam was measured according to the method specified in JIS K 6400. The elongation at break is preferably 150% or more, and more preferably 150% to 200%.
[0069] (4) Thermal conductivity The polyurethane foam of each example was cut into a rectangular parallelepiped shape of 200 mm (length) x 200 mm (width) x 35 mm (thickness) to prepare a test specimen. The thermal conductivity (W / m·K) of the test specimen was measured using a thermal conductivity measuring instrument ("AUTO-Λ HC-074", manufactured by Eiko Seiki Co., Ltd.) according to the method specified in JIS A1412-2. The lower the thermal conductivity, the better the insulation. The thermal conductivity should preferably be 0.025 W / m·K or less.
[0070] The components listed in Table 2 are as follows. <Polyol Composition (P)> (P-1) to (P-6): Polyol compositions (P-1) to (P-6) <Polyol> Polyol (a-1): Polyether polyol produced in Production Example 1 <Organic polyisocyanate (B)> (B-1): Product name "Coronate T-80" (manufactured by Nippon Polyurethane Industry Co., Ltd.), TDI <Foaming agent (C)> (C-1):Water <Catalyst (D)> (D-1): "TEDA-L33" manufactured by Tosoh Corporation, triethylenediamine / dipropylene glycol = 33 / 67 wt% solution (D-2): "TOYOCAT ET" manufactured by Tosoh Corporation, bis(2-dimethylaminoethyl) ether / dipropylene glycol = 70 / 30 wt% solution (D-3): "Neostan U-28" manufactured by Nitto Kasei Co., Ltd., stannous octylate <Foam stabilizer (E)> (E-1): Toray Dow Corning "L-580"
[0071] [Table 2]
[0072] As shown in Table 2, the polyurethane foams of Examples 1 to 6 had lower thermal conductivity and better insulation than the polyurethane foams of Comparative Examples 1 and 2. The polyurethane foams of Examples 1 to 6 had higher tensile strength and better strength than the polyurethane foam of Comparative Example 1. The polyurethane foam of Comparative Example 2 had high tensile strength, but high thermal conductivity and poor insulation. These results show that the present invention can provide polyurethane foams with excellent insulation and strength, and a method for producing the same.
Claims
1. A polyurethane foam obtained by reacting materials including a polyol component (A), an organic polyisocyanate component (B), a blowing agent (C), a catalyst (D), a foam stabilizer (E) and hollow particles (F), The polyol component (A) satisfies all of the following (1) to (3), A polyurethane foam having a hollow particle (F) content of 5 to 30% by weight based on the weight of the polyurethane foam. (1) the polyol component (A) has a hydroxyl value of 25 to 60 mgKOH / g; (2) the number average functionality of the polyol component (A) is 3 to 4; (3) The weight proportion of oxyethylene units contained in the polyol component (A) is 20% by weight or less based on the weight of the polyol component (A).
2. The polyurethane foam according to claim 1 , wherein the material further comprises a dispersing agent (G).
3. Polyurethane foam core density (kg / m 3 2. The polyurethane foam according to claim 1, wherein the molecular weight of the polyurethane foam is 30 to 50.
4. A method for producing the polyurethane foam according to claim 1, comprising the steps of: Step 1 of preparing a polyol composition containing a polyol component (A) and hollow particles (F); and step 2 of reacting the polyol composition with an organic polyisocyanate component (B) in the presence of a blowing agent (C), a catalyst (D) and a foam stabilizer (E).
5. The method for producing a polyurethane foam according to claim 4, wherein a dispersant (G) is used in step 1.
6. Polyurethane foam core density (kg / m 3 5. The method for producing a polyurethane foam according to claim 4, wherein the molecular weight of the polyurethane foam is 30 to 50.
Citation Information
Patent Citations
Composition for forming polyurethane foam, polyurethane foam, and thermal insulating material
JP2022064050A
